(untitled) (Global Journal of Human-Social Science, 2017)
Throughout the world today depletion of natural resources is among the major problems facing human beings Land degradation especially in the highlands has been identified as the most serious environmental problem in Ethiopia The Hararghae highlands in Eastern Ethiopia Tigrai Wollo and Semen Shoa highlands in the north and the Gamo-Gofa highlands and the Bilate River basin which starts in eastern slopes of Gurage highlands and stretches through eastern Hadiya and Kembatta highlands are some of the seriously eroded degraded land surfaces in Ethiopia The dominant man induced causes of land degradation in Ethiopia are poor farming practices population pressure overgrazing over cultivation soil erosion deforestation salinity and alkalinity problems and the use of livestock manure and crop residue for fuel as energy resource of the rural households The recorded annual soil erosion surface soil movement in Ethiopia ranges from low of 16 tons ha yr to high of 300 tons ha yr depending mainly on the slope land cover and rainfall intensities The total estimated annual soil loss surface soil movement from the cultivated range and pasture lands 780 000 km 2 in Ethiopia is estimated to range from low of 1 3 to an average of 7 8 billion metric tons per year Study put the degraded area on the highlands at 27 million ha of which 14 million hectares is very seriously eroded with 2 million ha of this having reached a point of no return and the soil depth is so reduced that the land is no longer able to support any vegetative cover Land degradation costs indicators are reduced yield change in land-use and change in crops abandonment of fields and altered livestock mixes and patterns of grazing flooding changes in stream flow silting of rivers dams unreliability of irrigation water flow and decline in quality of drinking water and ground water loss of environmental services migration and associated loss of human capital and break up of co